Rainfall-runoff model calibration and daily streamflow simulation for an ungauged catchment - 289048 Zamri Mohd (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Master of Engineering (Hydrology and Water Resources)) - Universiti Teknologi Malaysia, 2000